(3QSGFd GdOQhRs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hGdYGbHI def JjbX ef hSf GdZGajf hGfJbd Yf Lgd GdLGgdjf hGNdU efg Gdjbjf aHGOQ HGdJhHI Edi Gddg JYGdi s
(3BNQgG (B:s
(3GdMGce GdGMO GdaQO GdUeO GdefRg Yf GdUGMHI hGdhdO SHMGfg hJYGdi YeG jUahf hjYJbOhf ajg GdedMOhf hjJbhdhf GdeTQcjf YdhG cKjQkG GfJgi GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis